2016
DOI: 10.1213/ane.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Anesthesia Workforce Survey: A 30-Year Update

Abstract: Since 2001, there have been significant changes in how responding hospitals provide obstetric anesthesia care and staff the labor and delivery ward. Obstetric anesthesia surveys, updated every 10 years, continue to provide information about changes in obstetric anesthesia practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 31 publications
0
55
1
5
Order By: Relevance
“…We found that NAL use increased substantially during our multi-year program but is significantly less than the 60% rate cited for developed countries such as the USA (1). Our multi-year collaboration achieved greater success than that reported by Kopic et al (12) following their one-time intervention (from 1.2 to 2.3%), but the overall rate of approximately 10% we saw in 2015 is considerably less than the 45% rate reported by Ninidze et al (10) at the end of their multiyear intervention.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We found that NAL use increased substantially during our multi-year program but is significantly less than the 60% rate cited for developed countries such as the USA (1). Our multi-year collaboration achieved greater success than that reported by Kopic et al (12) following their one-time intervention (from 1.2 to 2.3%), but the overall rate of approximately 10% we saw in 2015 is considerably less than the 45% rate reported by Ninidze et al (10) at the end of their multiyear intervention.…”
Section: Discussioncontrasting
confidence: 62%
“…The use of regional anesthesia (RA) for cesarean delivery (CD) has become widespread in countries in the USA and in Western Europe (1, 2). RA is associated with a lower maternal mortality risk compared to general anesthesia (GA) in both high and low- and middle-income countries (LMICs) (37).…”
Section: Introductionmentioning
confidence: 99%
“…32 Because our multilevel model adjusts for case mix, we suggest that increased use of general anesthesia during weekend may be related to understaffing or provision of care by less experienced physicians. 33,34…”
Section: Patient-level Factors Associated With General Anesthesiamentioning
confidence: 99%
“…It is unclear whether similar results would be seen for higher‐risk women or women undergoing cesarean delivery after a trial of labor, and further studies are needed. The very high rate of general anesthesia in each group is another demerit of this study as this practice is not consistent with obstetric anesthesia practices in Western Europe or North America, where rates of neuraxial anesthesia are substantially higher for elective CS . The use of intraoperative and postoperative exclusion criteria raises concerns about selection bias and nonutilization of intention‐to‐treat analysis; these criteria were used to avoid the inclusion of women with increased perioperative blood loss, which is not related to the mode of placental delivery.…”
Section: Discussionmentioning
confidence: 99%